Verapamil Parameter- and Dose-Dependently Impairs Memory Consolidation in Open Field Habituation Task in Rats - Popović, Natalija; Giménez de Béjar, Verónica; Caballero-Bleda, María; Popović, Miroljub (Frontiers in Pharmacology, 2017)
The purpose of the present study was to examine the effects of the phenylalkylamine class of the L-type voltage-dependent calcium channel antagonist, verapamil (1.0, 2.5, 5.0 or 10 mg/kg i.p.), administered immediately after the acquisition task, on memory consolidation of the open field habituation task, in male Wistar rats. On the 48 h retested trial, all tested parameters (ambulation in the side wall and in the central areas, number of rearing, time spent grooming and defecation rate) significantly decreased in the saline treated animals. A significant decrease of rearing was observed in all verapamil treated groups. On the retention day, the ambulation in the side wall and central areas significantly decreased in the animals treated with 1mg/kg and 10 mg/kg of verapamil, while the time spent grooming and the defecation rate significantly decreased only in the group treated with 1 mg/kg of verapamil. According to the change ratio scores that correct the individual behavioural baseline differences during initial and final sessions, habituation deficit was found in animals treated with verapamil as follows: ambulation along the side wall area (1, 2.5 and 5 mg/kg), number of rearing (all used dose) and time spent grooming (2.5, 5 and 10 mg/kg). In conclusion, the present data suggest that the post-training administration of verapamil, parameter- and dose-dependently, impairs the habituation to a novel environment.